L’ancrange linguistique de la polyphonie - Nølke, Henning (2013)
Linguistic studies of polyphony bloom and seem more important than seeking excavate the concept of language underlying the application of this metaphor. First of all, we noted that the starting point of the whole theory of linguistic polyphony seems to be the assumption that the polyphony of utterances leaves traces on the level of language. It is this assumption that makes the study interesting for the linguist. But what is the nature of these traits? I defend the hypothesis that the polyphony is anchored in the linguistic form itself, or more specifically, the linguistic system, the language engenders indications that refer to the polyphonic meaning of the utterances. The article consists of three parts. At first, I study the notion of linguistic anchorage and I propose a formalization and method for its study . Second, I present a brief introduction to ScaPoLine (Scandinavian theory of linguistic polyphony) that applies to this method , and in the third part, I offer some analysis of concrete examples of polyphony.